(untitled) (Revista Electrónica REDINE, 2025)
This study investigates the potential to use artificial intelligence (AI) to transform mathematics education for students with Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD) by providing adaptive, individualized learning experiences. The 12-week investigation, conducted with 187 neurodiverse students, employed AI-driven systems that, in real time, intellectually and emotionally tailored instructional content, feedback systems, and challenge levels to individual students. The findings demonstrated measurable academic and behavioral improvements: ASD students demonstrated a 28.4% improvement in abstract thinking when introducing algebraic concepts through interactive visualizations, and ADHD students reduced impulsivity-based errors by 32.1% through dual-validation mechanisms and adaptive timers. Along with academic gain, the study reported significant gain in executive functions such as working memory (+15.3 points) and inhibitory control (+12.7 points) and psychoaffective outcomes such as 29% fewer math anxieties. Such gains were credited to AI’s ability to personalize learning pathways—for instance, breaking down fraction problems into microsteps for ADHD learners or color-coding interfaces for sensory-sensitive ASD learners. The article concludes that AI, if neurodiversity-designed, can be a powerful cognitive empowerment tool, closing inclusive education gaps while emphasizing the immeasurable human educator role of complex student need interpretation.